Development of species identification techniques for anguillid eels using species-specific genetic markers - Eun Soo Noh; Chun Mae Dong; Hee Jeong Park; Eun Mi Kim; Hyo Sun Jung; Hee Jeong Kong; Young Ok Kim (Frontiers in Marine Science)
The decline in eel resources, coupled with the challenges of morphological identification and the rise of illegal trade, highlights the urgent need for accurate species identification techniques. To address this, a multiplex PCR assay was developed, targeting the mitochondrial Cytochrome b gene. Species-specific primers were designed and their efficacy validated through single PCR. The multiplex PCR conditions were then optimized to enable the simultaneous amplification of five major eel species. This assay exhibited high accuracy, specificity, and sensitivity, successfully identifying all five species even when DNA concentrations were low. This multiplex PCR assay offers a rapid and cost-effective solution for eel species identification, with the potential to significantly bolster eel conservation efforts. By enabling accurate species identification, it can help combat illegal trade and support the sustainable management of eel resources.